On within-couple time allocation: Gendered disparities in paid work and housework in Europe - Maryna Tverdostup; Alireza Sabouniha (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper aims to pursue a deeper understanding of gendered within-couple allocation of time into paid work and housework in heterosexual dual-earner couples. Relying on the second wave of Harmonised European Time Use Survey (HETUS) data for 10 European countries, we estimate spousal relative worktime and housework to analyse within-couple time-use arrangements. The results show that the disparity between a wife's and a husband's workhours is gradually narrowing, yet housework remains firmly gendered even in couples in which the wife works more hours than the husband. We document strong inertia in the wife's share of housework. Although it decreases as her labour market commitment increases, the decline is slow. In addition, even if it is approaching a gender-equal split, the withincouple division of housework barely passes the point at which the husband's contribution to housework surpasses that of his wife. These results suggest that gendered time division aligns broadly with traditional theories of the household, yet the role of the 'doing-gender' hypothesis is non-negligible.
Keywords: D10; J16; J22; J24; 330; paid work; unpaid work; gender gap; intra-family decisions; labour market outcomes; European countries